ANALISIS KETERAMPILAN MENULIS SEBAGAI BAGIAN DARI KETERAMPILAN BERBAHASA DI SEKOLAH DASAR - Desnora Sahriaty Siregar; Erna Ikawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Writing skills are a crucial aspect of language learning, playing a significant role in developing elementary school students' thinking, communication, and creativity skills. This study aims to analyze writing skills as an integral part of language learning, encompassing an understanding of the concept of writing, types of writing, and the steps students take in the writing process. The research method used was descriptive qualitative, with data collection techniques including observation, interviews, and document analysis of student writing. The results indicate that most students still experience difficulty expressing their ideas in a structured manner and in accordance with proper Indonesian language rules. Contributing factors include a lack of writing practice, limited vocabulary, and a limited understanding of the writing stages, from prewriting to revision. Teachers play a crucial role in guiding students through the implementation of engaging and contextual writing learning strategies. The study's conclusions emphasize that writing skills must be developed sustainably as part of a comprehensive language learning process, taking into account the process, types of writing, and students' communication needs at the elementary school level.